Design and development of hot-water treatment plant for mango (Bangladesh Journal of Agricultural Research, 2008)
Postharvest loss of mangoes in Bangladesh ranges from 20 to 30 percent, mainly for lack of proper postharvest practices. As a result, quantitative as well as qualitative loss occurs. To reduce postharvest loss, a hot-water treatment plant for mango has been designed and developed at the Farm Machinery and Postharvest Process Engineering Division, Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur. Overall dimension of the plant is 3030 x 1000 x 814 mm and made of M S sheet, M S angle, bearing, chain, sprocket, electric heaters, cork sheet, pulley, etc. It has five main functional parts: i) rectangular tanks, ii) roller type conveyer assembly, iii) water heating system, iv) power transmission system, and v) agitator assembly. Conveyor roller is rotated by an electric motor and water is heated by six 3 kW immersion electric heaters. The digital temperature controller is set to control the temperature of water. The plant was tested for treating mango in Joydebpur and Chapai Nawabganj. Mangoes were treated at 55Â±1Â°C for 5 minutes. The average capacity of the plant was 1,088 kg per hour. The cost of hot water treatment wasonly Tk. 0.17 per kg. No anthracnose or stem-end rot disease was observed. Most of the mangoes had attractive colour and the shelf-life was increased upto10 days. The postharvest loss was only 0.13 percent. The farmers, traders, and exporters will be benefited using this plant. The break-even-point of the plant was only 5.5 tons of mangoes per year. Price of the plant was Tk. 75,000.Bangladesh J. Agril. Res. 32(4) : 637-648